The implementation of the integrative approach in determining educational planning goals and objectives at SMK Taruna Bakti Baturraden - Nurdiansyah, Muhammad Hafidza Daffa (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This research investigates the educational planning mechanism at Taruna Bakti Vocational High School Baturraden, the only vocational school in the Baturraden area. As a new institution, it plays a crucial role in vocational education. Methods: A qualitative approach is utilized, combining literature reviews and case studies. Interviews are conducted as the primary data collection method. The instruments used include interview guidelines, online communication tools, and direct interaction with the researchers. Findings: SMK Taruna Bakti Baturraden applies SWOT analysis to develop its educational planning documents. This strategic tool helps the school identify strengths, weaknesses, opportunities, and threats to guide its educational development and planning process. Conclusion: The educational planning process at SMK Taruna Bakti Baturraden is informed by SWOT analysis, offering a structured approach to planning in the school’s development. This methodology supports effective decision-making and adapts to the school’s unique position as a new institution in the area. Novelty/Originality of this Study: This study offers a unique exploration of how SWOT analysis is used in the educational planning process at a new vocational high school. It provides insights into how new institutions can strategically plan their development to address both challenges and opportunities in the education sector.